Cluster Analysis to the Factors Related to the Dissemination of Information About Healthy Eating in a School Population of Young Adolescents - P. F.Guiné, Raquel; R. Fernandes, Sofia (Current Nutrition & Food Science, 2016)
Background: Eating behaviours are essential for the healthy development of adolescents, both physically and also to the formation of their identity. Eating habits, in turn, are influenced by a wide variety of factors, including knowledge, attitudes, lifestyle, family, sociodemographic and behavioural factors. Hence, the objective of this study was to evaluate how the young adolescent students get information about healthy eating. Methods: A descriptive cross-sectional study was undertaken on a non-probabilistic sample of 345 students in Portuguese schools, aged between 13 and 15 years old. The techniques applied to the data were Principal Component Analysis (PCA), Factor Analysis (FA) and Cluster Analysis (CA), using SPSS software. For validation of the final solution some tests were used: Chi square and Kruskal Wallis, considering a level of significance of 5%. Results: Factor analysis allowed concluding that the variables used to assess the sources of information about healthy eating can be grouped into two factors: one linked to learning outside of school and the other associated with learning in school. The Cronbach's alphas were 0.661 and 0.676, respectively. Cluster analysis showed that the adolescents can be divided into four groups: cluster 1 – students well informed both by school and external sources; cluster 2 – students misinformed either by school or by external sources; cluster 3 – students misinformed by school but well informed by external sources, cluster 4 – students well informed by school but barely by external sources. Conclusion: The findings in the present work may allow improving the way information about healthy eating can reach the adolescents, and hence improve their general degree of knowledge and wellbeing.
Keywords: factor analysis